Overcoming Boredom with a Better Work Environment in Indonesia: Mengatasi Kebosanan dengan Lingkungan Kerja yang Lebih Baik di Indonesia - Afiyanto, Muhammad Alfin; Putra , Boy Isma (Universitas Muhammadiyah Sidoarjo, 2024)
CV. Lima Cahaya, a printing services company, faced a significant increase in employee-related complaints from 2021 to 2022, primarily due to lack of thoroughness linked to boredom. This study aimed to analyze the impact of physical and non-physical work environments and psychological conditions on employee boredom. Using a questionnaire completed by 20 employees and analyzed through multiple linear regression and Importance Performance Analysis (IPA), results showed that improvements in the work environment significantly reduce boredom (Y=0.721+0.547X1+0.339X2+0.088X3). The high satisfaction levels (above 80%) indicate that the current environment meets employee expectations, providing insights for management to enhance employee performance and reduce complaints. Highlight: Complaint Rise: 37% increase in employee complaints due to boredom. Influential Factors: Work environment and psychological conditions affect employee boredom. High Satisfaction: IPA shows over 80% satisfaction with current work conditions. Keyword: printing services, employee boredom, work environment, multiple linear regression, Importance Performance Analysis